Determining the frequency and severity of malnutrition and correlating it with the severity of liver cirrhosis - Iftikhar Haider NAQVI; Khalid MAHMOOD; Sirajus SALEKEEN; Syed Tehseen AKHTER (Turkish Journal of Gastroenterology, 2019)
-